The relationship between five-factor model and diagnostic and statistical manual of mental disorder-fifth edition personality traits on patients with antisocial personality disorder - Mahdi Amini; Abbas Pourshahbaz; Parvaneh Mohammadkhani; Mohammad-Reza Khodaie Ardakani; Mozhgan Lotfi; Mohammad Arash Ramezani (Journal of Research in Medical Sciences, 2015)
Background: Despite the fact that new criteria of antisocial personality disorder (ASPD) in diagnostic and statistical manual of mental disorders-fifth edition (DSM-5) were resulted from five-factor model (FFM), there is a small amount of studies that investigate the relations between proposed personality traits and FFM. Also, cross-cultural study in this field continuously would be needed. The aim of the present study was to evaluate the relation between the FFM and DSM-5 ASPD pathological traits. Materials and Methods: This study was a cross-sectional study design. The participants consisted of 122 individuals with ASPD that selected from prisoners (73.0%), outpatients (18.0%), and inpatients (9.0%). They were recruited from Tehran Prisoners, and Clinical Psychology and Psychiatry Clinics of Razi and Taleghani Hospitals, Tehran, Iran, since 2013-2014. The Sample was selected based on judgmental sampling. The structured clinical interview for DSM-IV axis II disorders-Personality Questionnaire, NEO-Personality Inventory-Revised, and DSM-5 personality trait rating form were used to diagnosis and assessment of personality disorder. Pearson correlation has been used for data analysis. All statistical analyses were performed using the SPSS 16 software. Results: The results indicate that neuroticism (N) has positive significant relationship with hostility (r = 0.33, P < 0.01), manipulativeness (r = 0.25, P < 0.01), deceitfulness (r =.23, P < 0.01), impulsivity (r = 0.20, P < 0.05), and negative relation with risk taking (r = −0.23, P < 0.01). Also, there was significant relationship between extraversion (E) with manipulativeness (r = 0.28, P < 0.01) and deceitfulness (r = 0.32, P < 0.01). Agreeableness and conscientiousness have negative significant relation with DSM-5 traits. In addition, results showed that there is positive significant relationship between FFM and DSM-5 personality traits with DSM-fourth edition-text revision (DSM-IV-TR) ASPD symptoms (P < 0.01). Conclusion: Except manipulativeness, deceitfulness, and callousness, there is positively significant relationship between DSM-5 ASPD traits and DSM-IV-TR ASPD symptoms. The present study helps to understand the adequacy of dimensional approach to evaluation of ASPD pathology, specifically on Iranian sample.